Obesity and mortality: questions and controversy - Allison, David (Henry Stewart Talks, 2007)
The relationship between obesity and mortality rate is complex, Differences in associations and causal effects may exist both within and across species, Obesity is clearly associated with elevated mortality rate and this association is generally presumed to reflect causation, The epidemiological evidence regarding the effect of being overweight (but not obese) is less clear and more controversial, Epidemiological evidence on the effects of weight loss on mortality rate among obese persons is even less clear, Evidence seems to suggest that weight loss induced by methods generally recommended by the biomedical community will prolong life among obese persons, Data strongly suggest that losing body fat, as opposed to just body weight, is what conveys the presumed benefit of weight loss on longevity
Archived at 2021/02/25